Evidence behind the narrative: Critically reviewing the social impact of energy communities in Europe. (December 2022) - Bielig, Mona; Kacperski, Celina; Kutzner, Florian; Klingert, Sonja
Abstract: Energy Communities are playing an ever greater role in the European renewable energy transition. As an instrument for citizen-led transformation, they are associated not only with economic and environmental, but also with social benefits. However, it is unclear whether Energy Communities in Europe deliver on the positive social impact they promise. In this paper, we analyze the conceptual background of the social impact associated with Energy Communities and clarify the underlying constructs of community empowerment, social capital, energy democracy and energy justice. We conduct a systematic literature review and develop an overview of studies which measured social impact. Through classifying evidence along methods and constructs measured in an evidence gap map, we demonstrate where rigorous evidence is missing: from quantitative and experimental studies, and longitudinal and counterfactual designs, which should guide future research. We conclude with recommendations for both research and policy to promote the collection of robust evidence on the social impact of Energy Communities in Europe.